Incursion Recognition Mechanism Based on Secure Network System - A. Mohamed Divan Masood; S. K. Muthusundar (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Internet based computing dissimilar services such as server storage and applications are shared on the internet. This makes cloud computing one of the most promising and rapidly growing technologies. As it relies on sharing computer resources, it is prone to various security risks. Individual such security issue is Distributed Denial of Services attack on cloud. A DDos assault can begin from anyplace in the system and normally overpowers the casualty server by sending countless. This paper deals with the prevention of DDos attacks and how honey pot approach can be used in cloud computing to counter DDos attacks.